Job Relevant Information: Model Partisipasi Penyusunan Anggaran, Kinerja Manajerial Dan Budgetary Slack - Ana Sopanah; Riza Bahtiar Sulistyan; Mulyono Mulyono; Harnovinsah Harnovinsah (Universitas Muhammadiyah Malang, 2023)
Purpose: This study aims to empirically see how participation in village government budgeting has an impact on managerial performance and budgetary slack, as well as to analyze the role of job relevant information in moderating the effect of budgetary participation on managerial performance and budgetary slack Methodology/approach: This research is a quantitative research. Data analysis used a variant-based Structural Equation Model (SEM), namely Partial Least Square (PLS) or commonly called SEM-PLS. The total sample is 178 Village Heads in Pamekasan Regency, East Java. Findings: The results of the study show that participation in budgeting has a positive effect on managerial performance and budgetary slack. Job relevant information also has a positive effect on managerial performance and budgetary slack Practical implications: Unique findings show that job relevant information is not a moderation between budgeting participation and managerial performance and budgetary slack. Originality/value: The novelty of this research lies in job relevant information as a moderating variable on the relationship between budgeting participation and managerial performance and budgetary slack simultaneously, which has never been done in previous research. Besides that, this research is focused on village government which, according to researchers, is still receiving less attention.